Pelindungan Hukum Terhadap Hak Atas Kesehatan Pekerja Migran Indonesia Sebagai Kelompok Rentan - Rifki Alfian Wicaksono; Ahmad Khairun Hamrany; Guntar Mahendro; Ilham Pransetyo (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study was conducted to determine how legal protection of the right to health applies to Indonesian migrant workers using a normative research method with a legislative and conceptual approach through access to primary legal sources in the form of legislation and international conventions, secondary legal sources, both journals and scientific books, as well as non-legal materials such as encyclopedia or relevant non-legal journals. The findings of this study indicate that there is a lack of oversight regarding the fulfilment of health rights, the national health insurance system for workers is not integrated with relevant health conditions, and there are discriminatory actions regarding access to health services in the host country.